Prácticas discursivas en la escritura de mujer Observaciones sobre la narrativa española contemporánea - Potok, Magda (Romanica Silesiana)
Discursive Practices in Women’s Writing. Observations on Contemporary Spanish Fiction On the basis of contemporary Spanish women writers’ fiction we propose to investigate whether besides a series of specific themes there exist any “traits of femininity” inscribed in the literary discourse itself and what are their categories and characteristics. The category of gender is apparent in various aesthetic, narrative and formal examples such as psychological realism, firstperson narrative, fragmentarism, incoherent and disordered structures, or multi-perspectivism. Although it has assimilated some elements of the postmodern episteme and aesthetics such as the use of metanarrative references, the combination of different refined and popular literary genres or the technique of autofiction, the feminine discourse inclines towards narrative models deriving from the sentimental fiction, with its rhetoric of the extreme and exaggeration. Key words: contemporary Spanish fiction, womens’ literature, discursive practice, gender studies, postmodern narrative.